A standard and protocol for in-situ measurement of surface soil reflectance - Eyal Ben Dor; Bar Efrati; Or Amir; Nicolas Francos; Jonti Shepherd; Vahid Khosravi; Asa Gholizadeh; Aleš Klement; Luboš Borůvka (Geoderma, 2024)
This study introduces an innovative standard and protocol approach for accurate assessment and harmonization of undisturbed soil surface spectra under field conditions, achieving laboratory-grade precision, while minimizing systematic discrepancies. The SoilPRO® assembly was employed for its efficacy in precisely measuring seven different soil samples under similar field and laboratory conditions in six different laboratories. While some discrepancies were noted in and between field and laboratory measurements, aligning the laboratory measurements with a reference sample, Lucky Bay (LB) internal soil standard (ISS), significantly reduced variations across different laboratory settings. A similar approach was employed to align field spectra using a field ISS (FISS), which could be practically applied in the field and adjusted to the laboratory reference LB before utilization. Correcting to the FISS facilitated the alignment of field reflectance among the six laboratories and closely matched with laboratory ISS measurements adjusted to the LB standard. This alignment of field reflectance with ISS-corrected laboratory measurements represents a ground-breaking achievement in field soil spectroscopy, which suffers from instabilities. It not only ensures preservation of the soil surface condition in the field, but also enables objective comparisons with all soil spectral libraries (SSLs) measurements and robust harmonization of field spectral data from different sources. The suggested method masks out technical aspects of spectral measurements in the field and prepares the signals to be analyzed for the physicochemical characteristics of the soil surface. The current study marks the first use of a controlled method for soil-surface spectroscopy measurements, opening a path for the construction of in-situ field SSLs. This advancement represents a significant step toward obtaining more accurate and standardized soil analyses of diverse surface properties under field conditions.